Narrative review on detonation of ai-generated deep fakes and misinformation: a threat to politicians in Malaysia / Faezatul Adilah A Sabri - A Sabri, Faezatul Adilah (Faculty of Communication & Media Studies, 2024)
AI-generated content has been cropping up more frequently in politics and election campaigns, sometimes sowing confusion among voters and causing them to lose trust in the truthfulness of what is presented before them. Therefore, the purpose of this study to explore the pervasive threat posed by AI-generated deep fakes and misinformation targeting politicians in Malaysia, and its implications on public trust, democratic processes, and the integrity of information dissemination. This paper presents This study is based on qualitative data obtained through a Narrative Literature Review from 10 Google Scholar and 5 Scopus indexed sources from the year 2019-2023. The findings reveal deep fakes and AI-disinformation pose severe threats today to Malaysian politicians across partisan lines through tactics like election media manipulation, fraudulent statement impersonations, and fake imagery viralized. Targeted leaders exhibited loss of constituent trust, reputation damage, psychological pressures, diminished leadership efficacy and voter confidence from exposure to multiplying information threats driven by advancing technology rather than ethics. Politicians in Malaysia are already facing threats from deep fakes and made-up propaganda about them online. This causes the public to become confused about what is real and lose trust in leaders.